BUSINESS EFFECTIVENESS WITH THE VALUE OF PRAYER ON OPERATING INCOME IN PT. PRAWEDA SARANA INFORMATICS - Aziz, Roikhan Mochamad; Rahmadani, Vivi; Wibowo, Satrio Bayu; Ahmad, Nur; Fathimah, Zuni Maulida (Journal of Management Review, 2023)
ABSTRACT PT. Praweda Sarana Informatika is a company in the field of technology, using the DEA method and Islamic values as reflected in the prayer values of its employees during the 2018-2022 period and seeing the influence of input and output variables on the company's growth rate. The input variables used are the Accumulated Number of New and Renewal Customers and the Number of Leads (Potential Customers) Entering. As for the output variable itself, namely Operating Income. So that its effect on the effectiveness of performance can be seen using the calculation of the reflexivity of worship. The results of the study show the effectiveness of employee performance data, it can be concluded that the increase in the effectiveness of employee performance is in line with the increase that occurs in the value of worship. The peak of the increase in reflexivity values occurs in 2022, where the effectiveness of performance is seen from the output variable (operational income) which reaches a maximum point of 100% in line with a significant increase in the worship value of employees to 90%. So it can be calculated the value of the reflexivity is at a percentage of 90%.